THE INFLUENCE OF DIFFERENCES IN THE CONCENTRATION OF 70% ETHANOL EXTRACT OF YARROW LEAVES (Achillea millefolium L) IN GEL FORMULATION ON PHYSICAL PROPERTIES, PHYSICAL STABILITY, AND ANTIBACTERIAL ACTIVITY AGAINST Pseudomonas aeruginosa IN VITRO - Nasar, Nur Afni Syariah; Nafisah, Lina; Fu'adah, Intan Tsamrotul; Pomalingo, Dwina Ramadhani; Fauziah, Siva (Edu Masda Journal, 2025)
ABSTRACTMany infections are caused by bacteria, viruses, fungi, or other minor groups. One of the bacteria that can cause skin infections is Pseudomonas aeruginosa. Yarrow (Achillea millefolium L) is a plant that is empirically used to treat bleeding wounds on the skin. This research was conducted by testing the antibacterial activity of 70% ethanol extract and in gel dosage form at concentrations of 5%, 10%, and 15% using the disc diffusion method. The reference substance/positive control used is gentamicin, and the negative control is sterile distilled water. The research results show that antibacterial activity at a concentration of 5% provides an inhibition zone against Pseudomonas aeruginosa bacteria of 16.46 mm, while the gel formulation at a concentration of 15% effectively inhibits the growth of Pseudomonas aeruginosa bacteria with an inhibition zone of 22.69 mm. Stability testing of the gel formulation during storage did not show any changes in colour, taste, odour, or form organoleptically. Homogeneous gel preparations with appropriate pH, spreadability, and viscosity remained stable for 28 days at different temperatures.                                           ABSTRAKBanyak infeksi disebabkaan oleh bakteri virus, jamur, atau beberapa kelompok minor lainnya. Salah satu bakteri yang dapat menyebabkan infeksi kulit adalah bakteri Pseudomonas aeruginosa. Daun Seribu (Achillea millefolium L) merupakan tumbuhan yang secara empiris digunakan untuk mengobati luka pendarahan pada kulit. Penelitian ini dilakukan dengan uji aktivitas antibakteri terhadap ekstrak etanol 70% dan dalam bentuk sediaan gel dengan konsentrasi 5%, 10% dan 15% dengan menggunakan metode difusi cakram. Sebagai zat pembandingnya/Kontrol positif yang digunakan adalah gentamicin dan sebagai kontrol negatif adalah aquadest steril. Hasil penelitian  menunjukan bahwa aktivitas antibakteri dengan konsentrasi 5% memberikan zona hambat pada bakteri Pseudomonas aeruginosa  16,46 mm sedangkan dalam bentuk sediaan gel dengan konsentrasi 15% efektif menghambat pertumbuhan bakteri Pseudomonas aeruginosa dengan zona hambat 22,69 mm. Uji stabilitas sediaan gel  pada penyimpanan secara organoleptik tidak terjadi perubhan warna, rasa, bau dan bentuk. Sediaan gel homogen dengan pH, daya sebar dan viskositas sesuai selama 28 hari dengan suhu yang berbeda.